Mapping the Evolution of Students’ Submicroscopic Representations: A Correspondence Analysis of Solute–Solvent Interactions - Sidauruk, Suandi; Meiliawati, Ruli (FKIP Universitas Lampung, 2025)
Understanding the particulate nature of matter in solutions requires integrating macroscopic, submicroscopic, and symbolic representations, a domain in which students often encounter misconceptions. This study investigated high school students’ conceptions of solute-solvent particle behavior in sugar and sodium chloride (NaCl) solutions using student-generated drawings. A total of 253 students from Grades 10, 11, and 12 in Palangka Raya, Indonesia, participated in a descriptive-comparative cross-sectional study. The open-ended pictorial test was validated by experts (Aiken’s V = 0.91), demonstrated substantial inter-rater reliability (Cohen’s κ = 0.753 for SSR; κ = 0.779 for CIR; p < .001), providing strong evidence of construct validity. Students’ representations were categorized into two dimensions: (1) Spatial Structural Representations (SSR): Regular-Loose (Rel), Regular-Dense (Red), Random (Ran), and Invisible/Disappeared (Dis); and (2) Chemical Interaction Representations (CIR): Molecular (MOR), Partial Ionic (PIR), Scientific Ionic (SIR), and Complex Mixed Ionic (MIR). Chi-square analysis revealed a significant relationship between grade level and both representational dimensions (SSR: χ²(6) = 29.079, p < .001, Cramer's V = 0.24, inertia = 0.115; CIR: χ²(6) = 61.612, p < .001, Cramer’s V = 0.349, inertia = 0.244). Correspondence analysis further revealed a progressive conceptual shift: Grade 10 students predominantly depicted Regular-Loose (solid-like) structures, whereas Grade 12 students more frequently produced Random (scientific) representations. Similarly, development in CIR moved from molecular (MOR/PIR) to scientifically accurate ionic forms (SIR/MIR). These findings highlight the need for multi-representational, visually oriented instruction, such as animations, augmented-reality simulations, and drawing-based assessments, to support conceptual change and strengthen coherence across representation levels. Keywords: particulate nature of matter, solution chemistry, correspondence analysis, representational competence, conceptual change.